Responsabilidad social y calidad de servicios de la Municipalidad Distrital de Punchana 2025 - Cerron Rivera, Franz Harrison (2025)
The purpose of this research was to determine the relationship between social responsibility and service quality in the Punchana 2025 District Municipality. The study was basic, with a non-experimental, cross-sectional design. The sample included the entire population; that is, all 50 users of the Municipality. According to the results, of a total of 50 respondents, 14.0% responded that social responsibility is poor, and 46.0% said it is good. Regarding the variable "Service Quality," 10.0% responded that it is poor, and 50.0% said it is good. Furthermore, Spearman's Rho showed a moderate positive correlation (0.690) and a significance level of 0.000, which is less than 0.05, indicating a direct relationship between social responsibility and the quality of service of the Punchana 2025 District Municipality.